1997
DOI: 10.1364/ol.22.000439
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ferroelectric 180°-domain structures in BaTiO_3 by use of second-harmonic scattering

Abstract: We present a method of determining the distribution of sizes of ferroelectric 180 degrees domains in BaTiO(3), using second-harmonic scattering. We find that the domains are rods with approximately square cross sections that extend from the -c to the +c face of the crystal, with widths ranging from 2 to 150 mum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…[7][8][9] . Following this, Gopalan et al 10 and Barad et al 11,12 demonstrated the use of polarization diagrams to investigate the domain structures in KnbO 3 and B 14 Ti 3 O 12 .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] . Following this, Gopalan et al 10 and Barad et al 11,12 demonstrated the use of polarization diagrams to investigate the domain structures in KnbO 3 and B 14 Ti 3 O 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of experimental investigations was reported focusing on characterizing the ferroelectric domains and domain walls in BaTiO 3 [8][9][10][11][12][13][14][15][16] as well as in other ferroelectric materials [17][18][19][20]. Transmission electron microscopy, X-ray spectroscopy, as well as scanning force microcopy have been applied with very limited success though: In fact, none of these inspections was able to deliver some experimental data on the physical properties within the 180 domain wall of BaTiO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…One needs to make a statistical treatment of the data on domain widths, obtained from the whole surface of the structure, to make conclusion about its quality for a nonlinear optical application. On the other hand, the methods based on non-linear optical effects such as imaging via secondharmonic generation [9][10][11], domain mapping via terahertz wave form analysis [12], and the method based on spontaneous parametric down-conversion (SPDC) [13][14][15] are free of these disadvantages. Usually, an appropriate non-linear effect is taken as an initial probing process to test inner parts of a PP structure and to predict its general characteristics in other non-linear applications.…”
mentioning
confidence: 99%